2009
DOI: 10.1093/eurjhf/hfn018
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the impact of strict glycaemic control on myocardial diastolic function and perfusion reserve: a report from the DADD (Diabetes mellitus And Diastolic Dysfunction) study

Abstract: AimsMyocardial diastolic dysfunction (MDD) and impaired coronary flow reserve (CFR) are early signs of myocardial involvement in patients with diabetes. The important question of whether this may be reversed by glucose normalization has not been tested in a controlled clinical trial. We hypothesized that strict glycaemic control, particularly if insulin based, will improve MDD and CFR. Methods and resultsThirty-nine type 2 diabetes patients (mean age 61.0 + 7 years) with signs of diastolic dysfunction were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 39 publications
(37 reference statements)
1
49
1
3
Order By: Relevance
“…The study by von Bibra et al 26 showed that intensive metabolic control with insulin therapy resulted in improvements in diastolic but not in systolic function, whereas studies by others failed to demonstrate improvements in either diastolic or systolic function, using tissue Doppler and ejection fraction measures, despite better glycemic control. [27][28][29] Most of these studies examined intensified glycemic control over shorter periods of time than our study, and it is possible that these short periods of improved glycemic control were insufficient for detectable changes in cardiac function to occur.…”
Section: Impact Of Metabolic Control On LV Functionmentioning
confidence: 85%
“…The study by von Bibra et al 26 showed that intensive metabolic control with insulin therapy resulted in improvements in diastolic but not in systolic function, whereas studies by others failed to demonstrate improvements in either diastolic or systolic function, using tissue Doppler and ejection fraction measures, despite better glycemic control. [27][28][29] Most of these studies examined intensified glycemic control over shorter periods of time than our study, and it is possible that these short periods of improved glycemic control were insufficient for detectable changes in cardiac function to occur.…”
Section: Impact Of Metabolic Control On LV Functionmentioning
confidence: 85%
“…3 Their relative contributions to myocardial stiffness differ in HFREF and HFNEF; fibrosis and AGEs are more important in HFREF and high F passive is more prominent in HFNEF. 3 Like macrovascular complications, 11,12 DM-related diastolic LV dysfunction failed to improve during intensified glycemic control, 13 and because of this "hyperglyce-mic memory," involvement of epigenetic processes was recently suspected. 14,15 …”
Section: Iabetes Mellitus (Dm)-induced Diastolic Left Ventricularmentioning
confidence: 99%
“…42 Blood pressure prior to PCI was well controlled in all patients prior to PCI, however, intraarterial measured systolic and diastolic blood pressures at baseline was higher in nondiabetic controls and patients in BQ123 group, and remained higher in these two groups at the end of PCI procedure. Despite higher blood pressure, CFR was higher in patients receiving BQ123, indicating a positive effect of selective ET A blockade on myocardial microcirculation.…”
Section: Dovepressmentioning
confidence: 78%